HPV-related external genital lesions among men residing in Brazil - da Silva, Roberto Jose Carvalho (Braz J Infect Dis, 2017)
The aims of this study were to determine the incidence of external genital lesions (EGLs), specifically histologically confirmed condyloma (genital warts) and Penile Intraepithelial Neoplasia (PeIN), and genital HPV infection progression to EGLs among healthy men aged 18–73 residing in Brazil. Subjects included 1118 men enrolled in the HPV Infection in Men (HIM) study between July 2005 and June 2009. At each visit, EGLs were biopsied and subjected to pathological evaluation. HPV status in genital swabs and biopsies was determined by Linear Array and INNO-LiPA, respectively. Age-specific EGLs incidence and the proportion and median time to EGL development were estimated. Kaplan–Meier cumulative incidence rates at 6, 12, and 24 months were determined. During follow-up, 73 men developed an incident EGL. Men could develop multiple EGLs and there were 36 men with condyloma, 27 men with lesions suggestive of condyloma, six men with PeIN, and 20 men with non-HPV lesions. HPV-positive men who developed EGLs were younger (p = 0.002) than men that did not develop lesions. Among the 815 men with HPV infection, 4% progressed to EGL with the same HPV detected in the swab. During follow up, 15.7% of genital HPV-6 and HPV-11 infections progressed to condyloma (median progression time of nine months for HPV-6 versus 6.8 months for HPV-11). Approximately 1% of HPV-16 infections progressed to PeIN with a median progression time of 25 months. HPV types covered by the 4-valent HPV vaccine were detected in 82.3% and 83.3% of condyloma and PeIN, respectively. The high burden of HPV and high frequency of progression to disease underscores the need to offer HPV prophylactic vaccination to men to reduce the overall burden of infection and diseases caused by HPV.